2015
DOI: 10.1016/j.seizure.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Admissions to paediatric intensive care units (PICU) with refractory convulsive status epilepticus (RCSE): A two-year multi-centre study

Abstract: Thiopentone was the most commonly used anticonvulsant to treat RCSE on admission to PICU. Mortality was low and approximately 1 in 25 showed a new neurological deficit at the 30-day follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Excluding 1 study judged to be low quality (confined to cases of suprarefractory SE) did not significantly change the mortality (20%; 95% CI, 8.1%-31.9%; I 2 = 94.1%). In addition, there were 2 pediatric studies of RSE, one covering 2008 to 2009 with an overall mortality of 4.0% 68 and the other from 2011 to 2016 with an overall mortality of 4.7%. 69 There was no significant evidence of a small-study effect from the Egger test results (5.39; 95% CI, −2.38 to 13.16; P = .11; eFigure 12 in the Supplement).…”
Section: Refractory Sementioning
confidence: 99%
“…Excluding 1 study judged to be low quality (confined to cases of suprarefractory SE) did not significantly change the mortality (20%; 95% CI, 8.1%-31.9%; I 2 = 94.1%). In addition, there were 2 pediatric studies of RSE, one covering 2008 to 2009 with an overall mortality of 4.0% 68 and the other from 2011 to 2016 with an overall mortality of 4.7%. 69 There was no significant evidence of a small-study effect from the Egger test results (5.39; 95% CI, −2.38 to 13.16; P = .11; eFigure 12 in the Supplement).…”
Section: Refractory Sementioning
confidence: 99%
“…A consistent finding across multiple studies is that the highest incidence of SE and refractory SE (RSE) is among children under 2 years of age. [1,[6][7][8][9][10] This may be due to a higher rate of symptomatic causes of SE, the natural course of genetic/metabolic diseases, or an increased susceptibility to seizures in the developing brain [11,12].…”
Section: Incidencementioning
confidence: 99%
“…When children with SE continue to have seizures despite two appropriate antiepileptic drugs, it is called refractory SE (RSE), which is covered in depth elsewhere in this volume [83]. The incidence of RSE ranges from 12 to 40% of all cases of SE [9,28] RSE that continues for 24 h or more after hospitalization is often called "super refractory SE" [28] or "malignant SE" [29]. Super refractory SE is uncommon, occurring in 10-15% of all cases of SE admitted to the hospital [28].…”
Section: Response To Treatmentmentioning
confidence: 99%
“…Different results are presented in the literature about the etiology of SE, according to age groups, the origin of the reports, and the classification of etiology [13]. Tully et al showed that prolonged febrile seizure was most common at 1-5 years, and remote symptomatic seizure was most common at 5-10 years [14]. In other studies, whereas febrile or acute symptomatic causes were frequently seen under two years of age, remote symptomatic seizures were more common in children two years and older [1,15].…”
Section: Se Is the Most Common Neurological Emergency Of Childhood And Requires The Appropriate Administration Of Aeds For Prompt Controlmentioning
confidence: 99%